Typical cases of violations of Russian speech etiquette norms by Chinese students - Gao, Fantao (University Pedagogical Journal, 2024)
The problem of teaching Chinese students of philology the rules of Russian speech behaviour is considered. The methodology of conducting a survey and the results of its verification are described. The mistakes caused by the violation of the norms of Russian speech etiquette by Chinese students in the main situations of communication are analysed.
Keywords: speech etiquette; Russian as a foreign language; professional training of philology students; ascertaining summary; typical mistakes